FAN1 interaction with ubiquitylated PCNA alleviates replication stress and preserves genomic integrity independently of BRCA2 - Antonio Porro (Nature Portfolio, 2017)
FANCD2-associated nuclease 1 (FAN1) is a key protein involved in the metabolism of DNA and in human pathologies. Here, the authors show that FAN1 directly interacts with PCNA at stalled replication forks to control their progression and prevent their collapse.